Gothic Arch Method to Establish Centric Relation - Rosalia Rey; Monica Fernandez; Eric Weber (Association of American Medical Colleges, 2015)
Abstract This video was created to enhance students' visual and conceptual ability in their complete denture course to see and relate clinically a different method of maxillo-mandibular recording relations in complete denture fabrication related to this patient visit. The material was also designed as a video review to compensate for the time between initial instruction and clinical application with patients. The authors created this 7-minute video file for students learning the use of the central bearing device as well as for practitioners interested in this type of maxillo-mandibular recordings. This method of making centric relation registration with eccentric movement is very informative for students' understanding of fundamental occlusal theory and its application to the treatment of edentulous/dentate patients. The centric relation gothic arch instructor guide and video can be used for formal instruction by faculty in dental courses, independent study/review by dental students prior to patient care, formal instruction in continuing dental education courses for general practitioners, and faculty calibration of student instructions.